The Influence Of Inflation, Exchange Rate, And Foreign Exchange Reserves On The Ship Unloading Of Garlic Threw Surabaya Harbour - Abha, Afifuddin (Archives of Business Research, 2019)
Indonesia is known as one of the world’s largest spice-producing countries which was once had self-sufficiency in garlic, but now have to import garlic from abroad to meet the needs of domestic garlic. Surabaya is the capital city of East Java Province in Indonesia known as the center of Eastern Indonesia which has a substantial contribution to the national economy. This research attempts to analyze the influence of inflation, Rupiah exchange rate and foreign exchange reserves towards the ship unloading of garlic simultaneously and partially. Analysis technique used are multiple linear regression analysis method and for the hypothesis test, F-test and t-test are used with significance level of 5%. As for the classic assumption test, this research uses normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. This research uses secondary data obtained from Statistic Bureau of East Java. The simultaneous test by F-test shows that inflation, rupiah exchange rate, and foreign exchange reserves significantly influence the import of garlic in East Java over the year 2012-2017 but foreign exchange reserves does not significantly influence the ship unloading of garlic threw Surabaya Harbour over the year 2012-2017.